PUBLICATIONS OF THE WEEK. (Bookseller, 2004)
This article presents information about books published this year. This list of books is prepared by the company Nielsen BookData. Some of the books include: "A Colour Handbook of Pests and Diseases of Peas and Beans," by Anthony J. Biddle and Nigel C. Cattlin, "Airline Operations and Scheduling," by Massoud Bazargan, "Understanding Flying Weather," by Derek Piggott, "Invention and Innovation," edited by Janine Bourriau and Jacke Phillips, and "Civilization One: Uncovering the Super-Science of Prehistory," by Christopher Knight and Alan Butler.